Global Economic Crisis and the Politics of Diversity
XV, 319 p.
Keywords: An interdisciplinary group of scholars from the global North and South critically explore the global deepening of market economy models. In case studies including Asia, the Middle East and Latin America, they examine the associated tensions of livelihood and ecology in the current context of global economic crisis, considering issues of natural ecology, water use, health, childcare, technology and work, migration, and economic growth. The analysis of the complex connections between domestic and global dynamics across diverse cases and issues helps reveal that state-centric approaches are still hovering over the politics of restructuring through which conformity to economic growth is addressed.